The impacts of religious identity on the relationship between workplace stress and inner meaning fulfillment among non-academic staff in Malaysia - Abdul Razak, Abdul Latif; Abdul Razak, Mohd Abbas; Salami, Mutiu (IIUM Press, International Islamic University Malaysia, 2018)
Modern-day working environment is often characterized with numerous and dynamic challenges for workers due to high expectation from the management, competition, and a host of other factors. This brings about the possibility of workers experiencing some emotional and psychological abyss (like stress, anxiety, and irritability) which calls for existential and psychological intervention in the workplace. Hence, this study examines the effects of religious identity on the relationship between workplace stress and inner meaning fulfillment (IMF). 148 non-academic staff from a public university in Peninsula Malaysia participated in the study. Data were collected with some quantitative set of questionnaires. Results reveal there is a significant negative correlation between workplace stress and IMF which means that workers with high inner meaning fulfillment experiences less stress at work. Also, it was found that workers with higher religiosity do experience inner meaning fulfillment. Implications from this study reveals the necessity of incorporating religiosity and existential constructs into any intervention approach for organizational and workers well-being. Suggestions and directions for future research were also discussed.